ON NONLINEAR PROPAGATION OF A TWO-DIMENSIONAL WAVE - Kamil Atabayev (Bright Mind Publishing, 2025)
The paper considers a plane problem of the motion of a monotonically decreasing load at supersonic speed D along the boundary of a half-plane, the material of which is modeled by an ideal medium with nonlinear and plastic properties.
Keywords: Plane problem, supersonic speed, ideal medium, half-plane, shock wave, unloading, load profile, stationary and in the unloading region, moving coordinates.